Addition of volatile sulfur compounds to yeast at the early stages of fermentation reveals distinct biological and chemical pathways for aroma formation. (August 2020) - Kinzurik, Matias I.; Deed, Rebecca C.; Herbst-Johnstone, Mandy; Slaghenaufi, Davide; Guzzon, Raffaele; Gardner, Richard C.; Larcher, Roberto; Fedrizzi, Bruno
Abstract: Volatile sulfur compounds (VSCs) greatly influence the sensory properties and quality of wine and arise via both biological and chemical mechanisms. VSCs formed can also act as precursors for further downstream VSCs, thus elucidating the pathways leading to their formation is paramount. Short-term additions of exogenous hydrogen sulfide (H2 S), ethanethiol (EtSH), S-ethylthio acetate (ETA), methanethiol (MeSH) and S-methylthio acetate (MTA) were made to exponentially growing fermentations of synthetic grape medium. The VSC profiles produced from live yeast cells were compared with those from dead cells and no cells. Interestingly, this experiment allowed the identification of specific biochemical and/or chemical pathways; e.g. most of the conversion of H2 S to EtSH, and the further step from EtSH to ETA, required the presence of live yeast cells, as did the conversion of MeSH to MTA. In contrast, the reaction from MTA to MeSH and ETA to EtSH was due primarily to chemical degradation. Ultimately, this research unravelled some of the complex interactions and interconversions between VSCs, pinpointing the key biochemical and chemical nodes. These pathways are highly interconnected and showcase the complexity of both the sulfur pathways in yeast and the reactive chemistry of sulfur-containing compounds. Highlights: Volatile sulfur compound accumulation involves biochemical and chemical reaction. Acetylation of ethanethiol and methanethiol requires live yeast. H2 S, ethanethiol and methanethiol are key nodes forming downstream VSCs.